The factors associated with entry to formal care for the elderly in Scotland: A longitudinal analysis - Corby, D. Helen; Everington, Dawn; Starr, John; Deary, Ian J.; Dibben, Chris (International Journal of Population Data Science, 2018)
Background Losing independence is a concern for older people, and sadly a reality for many. In Scotland there is an ageing population and unlike the rest of the UK, a policy to provide free personal and nursing care for those in need of assistance; this makes loss of independence high on the agenda of government, local authorities, care providers, older people and their families alike. Objectives This study aimed to investigate the factors associated with entry to formal care for older people in Scotland. In addition to socio-demographic, geographical and health characteristics, this study considered three lesser studied or novel factors: living in a flat, population density and recent employment. Methods A Scottish Longitudinal Study project (https://sls.lscs.ac.uk/) provided a 5.3% representative sample of the Scottish population for longitudinal analysis. This included people aged 65 and older in 1991 whose care-entry status was then followed-up in 2001. Findings Associations were found for age, sex, marital status, longterm illness, housing tenure, recent employment, urban/rural classification and population density. Notably, whilst living in rural areas had a protective association with formal care home entry (OR 0.35 [95% CI 0.29,0.43]), paradoxically, living in areas with a low population density was associated with greatly increased odds (OR 9.05 [95% CI 7.34, 11.19]). Conclusions This study indicates that the factors associated with care-entry in the Scottish population are similar to those in other Western countries. Possible explanations and justifications for the apparently paradoxical association found for population density are discussed. This finding might be relevant in populations outside Scotland, and future research should explore this.